2017
DOI: 10.1063/1.4974217
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low coercive field of improper ferroelectric Ca3Ti2O7 epitaxial thin films

Abstract: This paper was selected as Featured ARTICLES YOU MAY BE INTERESTED IN Interrelation between domain structures and polarization switching in hybrid improper ferroelectric Ca 3 (Mn,Ti) 2 O 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…This form of ferroelectricity should be prevalent in perovskiterelated materials because the octahedral rotations/tilts are ubiquitous structural distortions 21 (which are primarily of geometric origin and are driven by the size mismatch of the constituent ions). Indeed, a number of layered perovskites have been proposed as potential hybrid improper ferroelectrics through the integrated approach of symmetry arguments and first-principles calculations [22][23][24][25][26][27][28][29][30] , some of which have been experimentally confirmed to exhibit switchable polarization [31][32][33][34][35][36][37][38] , or at least crystalize in polar structures [39][40][41][42][43][44][45][46] . One can now utilize group theory to elucidate symmetry breaking caused by given distortions and identify whether their combinations result in a polar symmetry, and then the ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…This form of ferroelectricity should be prevalent in perovskiterelated materials because the octahedral rotations/tilts are ubiquitous structural distortions 21 (which are primarily of geometric origin and are driven by the size mismatch of the constituent ions). Indeed, a number of layered perovskites have been proposed as potential hybrid improper ferroelectrics through the integrated approach of symmetry arguments and first-principles calculations [22][23][24][25][26][27][28][29][30] , some of which have been experimentally confirmed to exhibit switchable polarization [31][32][33][34][35][36][37][38] , or at least crystalize in polar structures [39][40][41][42][43][44][45][46] . One can now utilize group theory to elucidate symmetry breaking caused by given distortions and identify whether their combinations result in a polar symmetry, and then the ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…In a report by Huang et al, the high‐energy antiphase boundaries and ferroelastic tilting and rotation domain walls were found to dominate the nucleation controlled kinetics of polarization flipping in a CTO single crystal . Very recently, employing pulsed laser deposition, Li et al deposited CTO thin films onto SrTiO 3 single‐crystal substrates and found that CTO film exhibits a coercive field of 5 kV/cm at a temperature of 2 K. While the coercive field of bulk CTO single crystal is around 120 kV/cm . The remnant polarization values of CTO have been reported to be 8, 0.6, and 8 μC/cm 2 for single crystal along the [100] direction, ceramic and thin film, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, employing pulsed laser deposition, Li et al deposited CTO thin films onto SrTiO 3 single‐crystal substrates and found that CTO film exhibits a coercive field of 5 kV/cm at a temperature of 2 K. While the coercive field of bulk CTO single crystal is around 120 kV/cm . The remnant polarization values of CTO have been reported to be 8, 0.6, and 8 μC/cm 2 for single crystal along the [100] direction, ceramic and thin film, respectively. Furthermore, those polarization characteristics were all probed and extracted from the so‐called positive‐up‐negative‐down (PUND) process.…”
Section: Introductionmentioning
confidence: 99%
“…Though these coercive fields are comparable to values suitable for integration to silicon chips (E c ≈ 50 kV cm −1 ), applications such as high-power actuators and low-voltage logic and memory elements ask for ferroelectrics with robust polarizations that can be switched by a lower coercive field [12][13][14][15] . Ultra-low coercive fields as low as 5 kV cm −1 were observed in pulsed laser deposition grown Ca 3 Ti 2 O 7 thin films, but the reason behind this reduction (and whether it is an intrinsic or an extrinsic effect) is not clarified yet 16 .…”
mentioning
confidence: 99%